Employee Retention Through Satisfaction and Engagement from Career and Compensation: Retensi Karyawan Melalui Kepuasan dan Keterlibatan dalam Karier dan Kompensasi - Luluk Lestari; Tantri Yanuar R. Syah (Academia Open, 2025)
General Background: Employee retention has emerged as a pressing concern for organizations amid increasing competition for skilled talent, particularly in knowledge-intensive sectors. Specific Background: While career development and compensation are widely recognized as key determinants of employee commitment, their indirect effects through psychological mechanisms remain underexplored in Indonesia’s industrial context. Knowledge Gap: Previous studies have largely examined these factors in isolation, within limited geographic or sectoral contexts, and rarely integrated job satisfaction and organizational engagement as dual mediators. Aim: This study investigates the extent to which organizational career development and compensation influence employee retention, with job satisfaction and organizational engagement as intervening variables, in the pharmaceutical manufacturing industry in Jakarta. Results: Using survey data from 221 millennial employees analyzed through PLS-SEM, the findings show that career development enhances job satisfaction, while compensation improves both job satisfaction and engagement. In turn, satisfaction fosters engagement and directly increases retention, although career development and compensation do not directly affect retention. Novelty: The research advances employee retention models by simultaneously integrating career development, compensation, satisfaction, and engagement in a multi-path mediation framework. Implications: Organizations should emphasize the tangible implementation of career pathways and transparent compensation systems to build satisfaction and engagement, thereby securing long-term retention.Highlight : Career development and compensation influence job satisfaction. Job satisfaction increases organizational engagement. Engagement and satisfaction together support employee retention Keywords : Organizational Career Development, Compensation, Job Satisfaction, Organizational Engagement, Employee Retention